What's so special about Lauren? : she's my baby sister - Moncure, Jane Belk.; Williams, Jenny, 1939- (Elgin, Ill. : Child's World ; Chicago, Ill. : Distributed by Childrens Press, 1987)
Lauren's big sister enjoys their times together, going places with the wagon, playing in the park, and dancing together.
Keywords: Sisters -- Fiction